A phase change composite material and its preparation method and application
By using a dual encapsulation structure and spirally wound high thermal conductivity yarn in phase change materials, the problems of insufficient thermal conductivity and leakage risks of traditional phase change materials are solved, efficient thermal management and energy storage are achieved, and the durability and reliability of the material are improved.
Patent Information
- Application Number
- CN202411720715.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The low thermal conductivity and stability of traditional phase change materials lead to major challenges in efficient thermal management, and at the same time there is a risk of leakage, affecting the reliability of equipment and systems.
Using a dual encapsulation structure, the phase change material is encapsulated in the inner core of the hollow polymer fiber, and the outer layer of the spirally wound graphitized carbonaceous yarn is enhanced to form an efficient three-dimensional thermal conductivity structure while ensuring the sealing and stability of the material.
It realizes efficient thermal management and energy storage, improves the thermal conductivity and mechanical properties of the material, reduces the risk of leakage, and ensures the durability and reliability of the material for long-term use.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a phase change composite material, in particular to a composite material with high thermal conductivity and phase change energy storage function, and a preparation method and application thereof. Background Art
[0002] Thermal management and energy storage technologies play an important role in many high-efficiency devices and systems. Especially in the fields of electronic equipment, building energy conservation, solar energy management and medical equipment, how to effectively regulate temperature and store energy has become a key research direction. Phase change materials, as a material that can absorb and release heat, are widely used in thermal management and energy storage. They maintain a relatively stable temperature in an environment with large temperature changes by storing and releasing heat during the phase change process. However, the low thermal conductivity and insufficient stability of traditional phase change materials still face great challenges in efficient thermal management.
[0003] In order to solve the problem of thermal conductivity of phase change materials, many researchers have tried to improve the thermal conductivity of phase change materials by adding high thermal conductivity materials (such as graphite, carbon fiber, etc.). However, these methods often have certain limitations. First, although the addition of high thermal conductivity fillers can improve thermal conductivity, these fillers usually have weak interactions with phase change materials, and the material is prone to delamination, shedding or migration during high temperature changes. Especially when the phase change material is liquefied or crystallized, due to insufficient interaction between the filler and the phase change material, the filler may be unevenly dispersed or aggregated, further affecting the efficiency and stability of thermal management.
[0004] In addition, after the phase change material is liquefied, there is a certain risk of leakage. Since most traditional phase change materials such as paraffin and polyethylene glycol are liquid at high temperatures, the leakage of the material may cause damage to the equipment or system, and even affect the environment. Especially when the phase change material is used in electronic equipment or building materials, its leakage may cause equipment failure or structural damage. Therefore, how to effectively prevent the leakage of phase change materials has become a major problem in thermal management and energy storage applications.
[0005] In order to solve these problems, the present invention proposes an innovative composite phase change material structure, which combines the advantages of high thermal conductivity materials and phase change materials, and provides a more efficient and reliable thermal management and energy storage solution. This solution is achieved by encapsulating the phase change material in the inner core of a hollow polymer fiber, and using a spirally wound outer layer of graphitized carbon yarn to enhance thermal conductivity. The design of the spiral structure not only effectively improves the thermal conductivity of the material, but also controls the directionality of heat conduction to evenly distribute the heat inside the material, thereby achieving efficient three-dimensional thermal conduction. In addition, due to the use of a double encapsulation structure, that is, the phase change material is encapsulated inside the hollow polymer fiber and further encapsulated by the carbon fiber spiral structure, the leakage problem of the phase change material can be effectively prevented.
[0006] The present invention solves the problem of leakage risk of traditional phase change materials through a double packaging structure. The packaging of hollow polymer fibers can effectively reduce the possibility of leakage of liquid phase change materials, while the spiral structure of the carbon yarn further enhances the overall sealing and mechanical strength of the material, preventing the risk of material deformation or leakage during the phase change process. Especially when the material undergoes multiple phase change cycles, this packaging structure can effectively ensure the sealing and stability of the phase change material, ensuring its durability and reliability in long-term use. Summary of the invention
[0007] In order to solve these problems, the present invention proposes a composite phase-change spiral composite material, which provides an efficient thermal management and energy storage solution by combining the advantages of high thermal conductivity materials and phase change materials.
[0008] Specifically, a first object of the present invention is to provide a phase change composite material.
[0009] The second object of the present invention is to provide a novel method for preparing a phase change composite material.
[0010] The third object of the present invention is to provide a novel application of phase change composite materials.
[0011] The present invention is achieved through the following technical solutions:
[0012] A phase change composite material comprises an inner core; the inner core is composed of hollow polymer fibers filled with organic phase change materials; and a graphitized carbon yarn with a tension of 1-3% is spirally wound on the surface of the inner core so that the hollow polymer fibers are in a compressed state; the hollow polymer fibers include at least one of thermoplastic polyurethane fibers, polypropylene fibers, polyvinyl alcohol fibers, polyvinylidene fluoride fibers or polycaprolactone fibers.
[0013] The organic phase change material is a mixture of alkanes having 18 to 30 carbon atoms; or
[0014] The organic phase change material is polyethylene glycol.
[0015] The alkane mixture having 18 to 30 carbon atoms is paraffin or a paraffin derivative.
[0016] The inner diameter of the hollow polymer fiber is 0.2-0.4 mm;
[0017] The outer diameter of the hollow polymer fiber is 0.3-0.6 mm.
[0018] The carbonaceous yarn is obtained by twisting a carbon nanotube film or a graphene film;
[0019] The twist of the carbon yarn is 3000-4000.
[0020] The surface of the yarn is coated with graphene;
[0021] The width of the carbon nanotube film or graphene film is 5-20 mm.
[0022] The method for preparing the phase change composite material comprises the following steps:
[0023] After the carbonaceous yarn is graphitized, the graphitized carbonaceous yarn is wound around the inner core to obtain a phase change composite material.
[0024] The method for preparing the graphitized carbon yarn comprises the steps of cutting a CNT film or a graphene film; twisting the CNT film or the graphene film into thin threads and connecting the ends thereof, twisting the threads again to obtain a yarn and graphitizing the yarn; or
[0025] The preparation method of the graphitized carbon yarn comprises the steps of cutting a CNT film or a graphene film; twisting the CNT film or the graphene film into thin threads and connecting the threads end to end, twisting the threads again to obtain yarns, loading graphene oxide and graphitizing the yarns.
[0026] The method for preparing the inner core comprises the steps of impregnating the hollow polymer fiber with a phase change material; or
[0027] The preparation method of the inner core comprises the step of coaxial wet spinning.
[0028] The method further comprises the step of surface treating the yarn coated with graphene oxide;
[0029] The surface treatment step includes multiple immersion and drying steps.
[0030] During the winding process, the speed of the synchronous motor, the moving speed of the slider and the yarn diameter satisfy the following formula:
[0031] T = 1000L / d;
[0032] Where T is the speed of the synchronous motor, L is the moving speed of the slider, and d is the yarn diameter;
[0033] The winding temperature is 180-200°C.
[0034] The phase change composite material is used for thermal management; or
[0035] For temperature regulation; or
[0036] Heat dissipation for electronic equipment; or
[0037] Devices for energy storage and conversion or
[0038] Used in temperature control and maintenance of medical equipment.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention provides a new type of phase-change composite energy storage material, which forms a composite material with high thermal management by using phase-change material as the inner core and spirally winding high thermal conductivity carbon nanotubes (CNT) or graphene yarns on the outer layer. This structural design not only prevents the possibility of phase-change material leakage, but also transforms the in-plane high thermal conductivity into the longitudinal direction through the spiral winding of the high thermal conductivity carbon film, effectively improving the longitudinal thermal conductivity of the material and meeting the demand for longitudinal thermal conductivity in practical applications.
[0041] 2. The composite phase-change energy storage material provided by the present invention has high thermal conductivity: by combining high thermal conductivity materials (such as CNT and graphene) with phase-change materials, the composite spiral structure has high thermal conductivity and the ability to quickly respond to temperature changes, which helps to quickly transfer heat, enabling it to effectively regulate temperature and store energy. Therefore, it can be used in thermal management and energy storage applications.
[0042] 3. The composite phase change energy storage material provided by the present invention has good mechanical properties and durability. The use of a carbon layer to heat-encapsulate the inner core can ensure the integrity and sealing of the material structure, thereby improving its durability in practical applications and being suitable for long-term use.
[0043] 4. The preparation of the composite phase change energy storage material provided by the present invention can be mass-produced. The method has simple steps, and the composite phase change energy storage material with excellent performance can be prepared by adjusting specific parameters. For example, through specific twisting, impregnation, drying and graphitization treatment steps, as well as precisely controlled winding and heat packaging processes, the quality and performance of the final product can be ensured.
[0044] 5. The composite phase change energy storage material provided by the present invention is applied to thermal management, which can improve thermal management efficiency, help reduce energy consumption, reduce greenhouse gas emissions, and meet the needs of global energy consumption and environmental protection.
[0045] 6. The composite phase change energy storage material provided by the present invention can be applied to the fields of building energy conservation, electronic equipment cooling, solar thermal management, etc. as a highly efficient thermal management and energy storage material. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The schematic diagram of the phase change energy storage composite material structure obtained by the present invention is shown;
[0047] Figure 2 A photo of the phase change energy storage composite material prepared in Example 1 of the present invention is shown;
[0048] Figure 3 A photograph showing the phase change energy storage composite material prepared in Example 1 of the present invention when it is bent;
[0049] Figure 4 The preparation device and process of the present invention are shown. DETAILED DESCRIPTION
[0050] The present invention provides a phase change composite material, wherein the inner core is enclosed in a carbonaceous yarn spirally wound on the surface of the inner core. At the same time, the inner core is composed of a hollow polymer fiber filled with a phase change material. This encapsulation method is a double encapsulation structure, that is, the phase change material is encapsulated in the hollow polymer fiber, and then the hollow polymer fiber is encapsulated in a spiral structure composed of carbonaceous yarn. Since the phase change material is encapsulated twice, the leakage rate of the phase change material will be greatly reduced. At the same time, the use of hollow polymer fibers for encapsulation will also improve the strength of the phase change composite material, so that after the phase change material is liquefied, the phase change composite material will not produce excessive deformation. This can ensure the integrity and sealing of the material structure, thereby improving its durability in practical applications and being suitable for long-term use. The use of carbonaceous yarn to form a spiral structure to further encapsulate the inner core can change the heat conduction direction of the phase change composite material. Because heat is conducted along the spiral structure, this can achieve three-dimensional heat conduction of the phase change composite material. If a carbonaceous film is used for encapsulation, only in-plane heat conduction in the carbonaceous film can be achieved. Specifically, the hollow polymer fiber includes one of thermoplastic polyurethane fiber, polypropylene fiber, polyvinyl alcohol fiber, polyvinylidene fluoride fiber or polycaprolactone fiber. Furthermore, since the volume of the phase change material usually expands when it is converted from a solid state to a liquid state, the hollow polymer fiber is in a state of being stretched. At this time, in some cases where bending is required, the hollow polymer fiber that is in a state of being stretched is bent again, and the surface of the hollow polymer fiber will be very easy to crack, and then crack, thereby causing leakage of the phase change material. If the tensioned carbonaceous yarn is spirally wound on the surface of the inner core, the spiral carbonaceous yarn will give the hollow polymer fiber a compressive stress, so that the hollow polymer fiber is in a compressed state and produces a certain deformation, and this deformation can be used to cope with the load on the hollow polymer fiber structure itself. When the phase change material is liquefied, the expansion it produces can be partially offset by the deformation caused by the hollow polymer fiber being in a compressed state. At this time, if the hollow polymer fiber is bent, the surface of the hollow polymer fiber is not easy to crack. Obviously, this will prevent the possibility of leakage of the phase change material and improve the reliability of the phase change composite material.
[0051] In certain specific embodiments of the present invention, the organic phase change material is a mixture of alkanes having 18 to 30 carbon atoms; or is polyethylene glycol.
[0052] In certain specific embodiments of the present invention, the organic phase change material is paraffin or a paraffin derivative.
[0053] In certain specific embodiments of the present invention, the inner diameter of the hollow polymer fiber is 0.2-0.4 mm; the outer diameter of the hollow polymer fiber is 0.3-0.6 mm.
[0054] In certain specific embodiments of the present invention, the carbonaceous yarn is obtained by twisting carbon nanotubes or graphene films; in the form of yarn, the three-dimensional thermal conductivity of the phase change composite material can be more effectively achieved. Preferably, the surface of the yarn is coated with graphene. After the graphene film or carbon nanotube film is rolled into a yarn, its surface has a reduced flatness due to the presence of curvature, and twisting will also produce defects on the surface of the film. Therefore, wrapping the graphene can improve the surface flatness of the yarn, thereby increasing the degree of connection between the fibers. At the same time, the presence of graphene can also increase the van der Waals force between the graphene layers that are closely adjacent to each other, thereby strengthening the mutual connection between the fibers.
[0055] Specifically, after graphitizing the carbonaceous yarn, the graphitized carbonaceous yarn is wound around the inner core to obtain the phase change composite material. Specifically, during winding, the carbonaceous yarn can be in a tensioned state and wound on the surface of the inner core by controlling the speed of the synchronous motor of the slider speed. During winding, the speed of the synchronous motor, the moving speed of the slider and the yarn diameter satisfy the following formula:
[0056] T = 1000L / d;
[0057] Where T is the speed of the synchronous motor, L is the moving speed of the slider, and d is the diameter of the yarn. At the same time, the carbon yarn is heated during winding so that its temperature during winding is 180-200°C, which is more conducive to the tensioning of the carbon yarn.
[0058] Specifically, the preparation method of the graphitized carbon yarn comprises: cutting a CNT film or a graphene film; twisting the CNT film or the graphene film into thin threads and connecting the ends, twisting the threads again to obtain the yarn and graphitizing the yarn; or loading graphene oxide and graphitizing the yarn after the yarn is twisted again. The loaded graphene oxide can be converted into graphene during graphitization, thereby filling the cracks generated on the surface of the CNT film or the graphene film when the film is twisted.
[0059] Specifically, the preparation method of the inner core can be prepared by impregnating the phase change material into the hollow polymer fiber, that is, filling the phase change material into the hollow polymer fiber under a vacuum state. For details, please refer to the vacuum impregnation method disclosed in the Chinese patent application disclosed as CN112724934A. Of course, other well-known methods can also be used for preparation, such as coaxial wet spinning. The Pu Xiong team of the Beijing Institute of Nanoenergy and Systems, Chinese Academy of Sciences, published a paper entitled "Core-Sheath CNT@MXene Fibers TowardAbsorption-Dominated Electromagnetic Interference Shielding Fabrics" in Advanced Fiber Materials, which adopted the coaxial wet spinning method.
[0060] Specifically, the carbonaceous yarn can be immersed in the graphene oxide dispersion liquid for multiple times to load the graphene oxide on its surface. After the immersion, the carbonaceous yarn is dried to remove the liquid in the graphene oxide dispersion liquid.
[0061] The phase change composite material provided by the present invention has a wide range of applications, and can be applied to thermal management; temperature regulation; heat dissipation of electronic equipment; and temperature control and maintenance of energy storage and conversion equipment or medical equipment.
[0062] The present invention is further described below in conjunction with specific embodiments.
[0063] The twist number in the examples refers to the number of twists per meter of the yarn.
[0064] Example 1
[0065] Composite phase change energy storage helical fiber without graphene loading
[0066] Step 1. Use CNT film to cut into CNT strips with a width of 14 mm. Fix one end of the CNT strip on the motor and the other end on the movable slider. Twist it into a thin wire (twist degree is 3000). Connect the thin wires end to end to obtain a long CNT thin wire A.
[0067] Step 2: subject the CNT thin wire A to high temperature graphitization treatment at 3000° C. to obtain the CNT composite thin wire B, and measure its diameter d.
[0068] Step 3: Use a polypropylene hollow fiber with an outer diameter of 0.4 mm and an inner diameter of 0.3 mm, and use a vacuum impregnation method to impregnate molten paraffin into the hollow fiber to obtain a composite fiber C (ie, the inner core).
[0069] Step 4: After the composite fiber C is stretched by 2%, it is installed on two synchronous motors with a spacing of 260 mm. The CNT composite wire B passes through the wire guide on the stepper motor and controls the slider speed to 200 mm / min. The synchronous motor speed T=1000L / d (T (rpm / min) is the synchronous motor speed, L (mm / min) is the slider movement speed, and d (μm) is the diameter of the composite wire C). The composite wire B is wound on the composite fiber C, and finally the two ends of the obtained sample are heat-sealed at 190°C to obtain a composite phase change energy storage material.
[0070] Comparative Example 1
[0071] Step 1. Use CNT film to cut into CNT strips with a width of 14 mm. Fix one end of the CNT strip on the motor and the other end on the movable slider. Twist it into a thin wire (twist degree is 3000). Connect the thin wires end to end to obtain a long CNT thin wire A.
[0072] Step 2: subject the CNT thin wire A to high temperature graphitization treatment at 3000° C. to obtain the CNT composite thin wire B, and measure its diameter d.
[0073] Step 3: Use a polypropylene hollow fiber with an outer diameter of 0.4 mm and an inner diameter of 0.3 mm, and use a vacuum impregnation method to impregnate molten paraffin into the hollow fiber to obtain a composite fiber C (ie, the inner core).
[0074] Step 4. Install the composite fiber C on two synchronous motors with a spacing of 260 mm. The CNT composite wire B passes through the wire guide on the stepper motor and controls the slider speed to 200 mm / min. The synchronous motor speed T = 1000L / d (T (rpm / min) is the synchronous motor speed, L (mm / min) is the slider movement speed, and d (μm) is the diameter of the composite wire C). Wind the composite wire B on the composite fiber C, and finally heat-package the two ends of the obtained sample at 190°C to obtain a composite phase change energy storage material.
[0075] Example 2
[0076] Composite phase change energy storage spiral fiber without graphene loading, the material is graphene film
[0077] Step 1. Use graphene film to cut into 14 mm wide graphene strips, fix one end of the graphene strip on the motor and the other end on the movable slider, twist it into a thin wire (twist degree is 3000), connect the thin wire end to end, and obtain a long graphene thin wire A.
[0078] Step 2: subject the CNT thin wire A to high temperature graphitization treatment at 3000° C. to obtain the CNT composite thin wire B, and measure its diameter d.
[0079] Step 3: Use a polypropylene hollow fiber with an outer diameter of 0.4 mm and an inner diameter of 0.3 mm, and use a vacuum impregnation method to impregnate molten paraffin into the hollow fiber to obtain a composite fiber C (ie, the inner core).
[0080] Step 4: After the composite fiber C is tensioned by 2%, it is installed on two synchronous motors with a spacing of 260 mm. The CNT composite wire B passes through the wire guide on the stepper motor and controls the slider speed to 200 mm / min. The synchronous motor speed T=1000L / d (T (rpm / min) is the synchronous motor speed, L (mm / min) is the slider movement speed, and d (μm) is the diameter of the composite wire C). The composite wire B is wound on the composite fiber C. Finally, the two ends of the obtained sample are heat-sealed at 190°C to obtain a composite phase change energy storage material.
[0081] Example 3
[0082] Phase change material is polyethylene glycol
[0083] Step 1. Use graphene film to cut into 14 mm wide graphene strips, fix one end of the graphene strip on the motor and the other end on the movable slider, twist it into a thin wire (twist degree is 3500), connect the thin wire end to end, and obtain a long graphene thin wire A.
[0084] Step 2: subject the CNT thin wire A to high temperature graphitization treatment at 3000° C. to obtain the CNT composite thin wire B, and measure its diameter d.
[0085] Step 3: Use a polypropylene hollow fiber with an outer diameter of 0.4 mm and an inner diameter of 0.3 mm, and use a vacuum impregnation method to impregnate molten polyethylene glycol into the hollow fiber to obtain a composite fiber C (ie, the inner core).
[0086] Step 4: After the composite fiber C is tensioned by 1%, it is installed on two synchronous motors with a spacing of 260 mm. The CNT composite wire B passes through the wire guide on the stepper motor and controls the slider speed to 200 mm / min. The speed of the synchronous motor is T=1000L / d (T (rpm / min) is the speed of the synchronous motor, L (mm / min) is the slider movement speed, and d (μm) is the diameter of the composite wire C). The composite wire B is wound on the composite fiber C. Finally, the two ends of the obtained sample are heat-sealed at 190°C to obtain a composite phase change energy storage material.
[0087] Example 4
[0088] Step 1. Use CNT film to cut into CNT strips with a width of 14 mm. Fix one end of the CNT strip on the motor and the other end on the movable slider. Twist it into a thin wire (twist degree is 4000). Connect the thin wires end to end to obtain a long CNT thin wire A.
[0089] Step 2: The long CNT wire A is stretched by a motor and immersed in a liquid tank containing a GO dispersion with a concentration of 0.03 mg / ml. After the immersion is completed, the CNT wire containing GO is passed through the infrared lamp area at a uniform speed for drying. The immersion and infrared drying are repeated twice, and the wire is wound on a bobbin after drying. The obtained bobbin is placed in a drying oven and dried at 75°C for 2 hours to obtain a GO@CNT composite wire B.
[0090] Step 3: The GO@CNT composite wire B is subjected to a high-temperature graphitization treatment at 3000° C. to obtain a G@CNT composite wire C, and its diameter d is measured.
[0091] Step 4: Use a polypropylene hollow fiber with an outer diameter of 0.4 mm and an inner diameter of 0.3 mm, and use a vacuum impregnation method to impregnate molten paraffin into the hollow fiber to obtain a composite fiber D (ie, the inner core).
[0092] Step 5. After the composite fiber D is stretched by 3%, it is installed on two synchronous motors with a spacing of 260 mm. The G@CNT composite wire C passes through the wire guide on the stepper motor and controls the slider speed to 200 mm / min. The speed of the synchronous motor is T=1000L / d (T (rpm / min) is the speed of the synchronous motor, L (mm / min) is the slider movement speed, and d (μm) is the diameter of the composite wire C). The composite wire C is wound on the composite fiber D. Finally, the two ends of the obtained sample are heat-sealed at 190°C to obtain a composite phase change energy storage spiral fiber.
[0093] Example 5
[0094] The difference between this embodiment and embodiment 4 is that in step 1, the CNT film is cut into strips with a width of 5 mm; the speed of the synchronous motor T in step 5 is 1000L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0095] Example 6
[0096] The difference between this embodiment and embodiment 4 is that in step 1, the CNT film is cut into strips with a width of 20 mm; the speed of the synchronous motor in step 5 is T=1000L / d, and the remaining steps and parameters are calculated based on the actual L and d and are consistent with those in embodiment 4.
[0097] Example 7
[0098] The difference between this embodiment and embodiment 4 is that in step 2, the long CNT wire A is stretched by a motor and immersed in a liquid tank containing a GO dispersion with a concentration of 0.01 mg / ml. After the immersion is completed, the CNT wire containing GO is passed through the infrared lamp area at a uniform speed for drying without repeated immersion. After drying, the wire is wound on the bobbin; the speed of the synchronous motor T in step 5 is 1000L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0099] Example 8
[0100] The difference between this embodiment and embodiment 4 is that in step 2, the long CNT wire A is stretched by a motor and immersed in a liquid tank containing a GO dispersion with a concentration of 0.05 mg / ml; the speed of the synchronous motor T in step 5 is 1000 L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0101] Example 9
[0102] The difference between this embodiment and embodiment 4 is that in step 2, immersion and infrared drying are repeated 4 times; the speed of the synchronous motor T in step 5 is 1000L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0103] Example 10
[0104] The difference between this embodiment and embodiment 4 is that in step 3, the GO@CNT composite wire B is subjected to a high-temperature graphitization treatment at 2000°C to obtain a G@CNT composite wire C; the synchronous motor speed T in step 5 is 1000L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0105] Embodiment 11
[0106] The difference between this embodiment and embodiment 4 is that in step 3, the GO@CNT composite wire B is subjected to a high-temperature graphitization treatment at 2500°C to obtain a G@CNT composite wire C; the synchronous motor speed T in step 5 is 1000L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0107] Example 12
[0108] The difference between this embodiment and embodiment 4 is that in step 4, a polypropylene hollow fiber with an outer diameter of 0.3 mm and an inner diameter of 0.2 mm is used; the speed of the synchronous motor T in step 5 is 1000 L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0109] Example 13
[0110] The difference between this embodiment and embodiment 4 is that in step 4, a polypropylene hollow fiber with an outer diameter of 0.5 mm and an inner diameter of 0.4 mm is used; the speed of the synchronous motor T in step 5 is 1000L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0111] Embodiment 14
[0112] The difference between this embodiment and embodiment 4 is that in step 5, the slider speed is controlled to be 100 mm / min; the synchronous motor speed T in step 5 is 1000 L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0113] Embodiment 15
[0114] The difference between this embodiment and embodiment 4 is that in step 5, the slider speed is controlled to be 300 mm / min; the synchronous motor speed T in step 5 is 1000 L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with embodiment 4.
[0115] Comparative Example 2 (low heat treatment temperature and low thermal conductivity)
[0116] The difference between this comparative example and Example 4 is that in step 3, the GO@CNT composite wire B is subjected to a high temperature treatment at 1500°C to obtain a G@CNT composite wire C; the speed of the synchronous motor T in step 5 is 1000L / d, which is calculated based on the actual L and d; the remaining steps and parameters are consistent with Example 4.
[0117] Comparative Example 3 (no heat sealing, a small amount of leakage)
[0118] The difference between this comparative example and Example 4 is that in step 5, after the composite fine wire C is wound on the composite fiber D (i.e., the inner core), the two ends of the obtained sample are not heat-sealed at 190°C; the speed of the synchronous motor T in step 5 is 1000L / d, which is calculated based on the actual L and d; the other steps and parameters are consistent with Example 4.
[0119] Comparative Example 4 (Fracturing due to excessive GO times)
[0120] The difference between this embodiment and embodiment 4 is that in step 2, immersion and infrared drying are repeated 5 times; the synchronous motor speed T in step 5 is 1000L / d, which is calculated based on the actual L and d; the other steps and parameters are consistent with embodiment 4. The sample obtained in this comparative example has fiber breakage during the spiral treatment due to excessive repeated immersion times.
[0121] The samples obtained from Examples 1-15 and Comparative Examples 1-3 were tested, and the test results are listed in Table 1 and Table 2:
[0122] 1. Observe the diameter d of the G@CNT composite wire C using a JSM-7610 scanning electron microscope;
[0123] 2. The axial thermal conductivity of the spiral fiber is calculated from the resistivity according to the formula K1=440000 / (ρ+258)-295, where ρ is the resistivity (microohm·cm) measured by the circuit board four-point method;
[0124] 3. The radial thermal conductivity of the spiral fiber is obtained by heat flow method and is recorded as K2;
[0125] 4. Fiber tensile strength test, characterized according to standard ISO 11566:1996;
[0126] 5. The latent heat of spiral fiber (h) is obtained by DCS test;
[0127] 6. Leakage rate test: take a section of composite spiral fiber as a sample and weigh it, record it as m0 (g). Heat the sample in a 90℃ oven, bend and straighten it every 2 hours and weigh it once, record it as m n (g), fiber leakage rate (%) is calculated according to the following formula, leakage rate = [(m0-m n ) / m0]×100%;
[0128] 7. In addition, it can be known from experimental rules that if the spirals are arranged closely, the speed of the synchronous motor needs to be adjusted according to the diameter of the composite wire C. The adjustment formula is T=1000L / d, T (rpm / min) is the speed of the synchronous motor, L (mm / min) is the moving speed of the slider, and d (μm) is the diameter of the composite wire C. The close arrangement of the spirals is beneficial to the improvement of thermal conductivity.
[0129] Table 1
[0130]
[0131] Table 2
[0132]
[0133] It can be seen from the sample data obtained in Examples 1-2 that the graphene coating layer is beneficial to improving thermal conductivity.
[0134] It can be seen from the sample data obtained in Examples 2-3 that the difference in phase change materials will directly lead to the difference in latent heat of the composite materials. The higher the latent heat of the phase change material, the higher the latent heat of the obtained sample, that is, more thermal energy can be stored.
[0135] From the sample data obtained in Examples 1 and 4-15, it can be seen that the samples obtained in the present invention have high thermal conductivity along the fiber direction and the fiber radial direction, and the composite phase change energy storage spiral fiber has good mechanical properties. In addition, the preparation method of the fiber can make it have strong anti-leakage ability;
[0136] It can be seen from Example 1 and Comparative Example 1 that after the carbonaceous yarn is stretched, the leakage of the organic phase change material can be effectively prevented.
[0137] From the sample data obtained in Examples 4-6, it can be seen that the spiral junction width, thermal conductivity, and tensile strength of the obtained spiral fibers increase with the increase of the CNT film width, while the latent heat of the spiral fibers decreases slightly with the increase of the CNT film width;
[0138] From the sample data obtained in Example 4 and Examples 7-9, it can be seen that the thermal conductivity and tensile strength of the obtained spiral fibers increase with the increase of the concentration of the GO dispersion or the number of immersion times;
[0139] From the sample data obtained in Example 4 and Examples 10-11, it can be seen that the graphitization temperature has a significant effect on the thermal conductivity of the spiral fiber. The higher the temperature, the higher the thermal conductivity.
[0140] From the sample data obtained in Example 4 and Examples 12-13, it can be seen that the larger the volume of the hollow cavity of the hollow fiber, the more phase change material is loaded, so the latent heat of the spiral fiber is higher; the smaller the outer diameter of the hollow fiber, the more beneficial it is to improve the thermal conductivity;
[0141] From the sample data obtained from Example 4 and Examples 14-15, it can be seen that the reduction of the moving speed of the slider of the stepper motor is conducive to the improvement of thermal conductivity;
[0142] It can be seen from the sample data obtained in Example 4 and Comparative Example 2 that when the heat treatment temperature of the composite fine wire B is too low, the thermal conductivity of the spiral fiber will be too low;
[0143] It can be seen from the sample data obtained from Example 4 and Comparative Example 3 that the lack of heat-sealing treatment on the end of the hollow fiber will lead to a decrease in the anti-leakage performance of the spiral fiber during the cyclic use;
[0144] In addition, the phenomenon in Comparative Example 4 shows that too many GO immersion times will eventually increase the rigidity of the fiber, making it easy to break during the spiraling process.
Claims
1. A phase change composite material, characterized in that: comprising an inner core; the inner core being composed of a hollow polymer fiber filled with an organic phase change material; and Tensioning 1-3% of graphitized carbon yarn, which is spirally wound on the surface of the inner core, so that the hollow polymer fiber is in a compressed state; The hollow polymer fiber includes at least one of thermoplastic polyurethane fiber, polypropylene fiber, polyvinyl alcohol fiber, polyvinylidene fluoride fiber or polycaprolactone fiber; The preparation method of the phase change composite material comprises the following steps: After graphitizing the carbonaceous yarn, the graphitized carbonaceous yarn is wound around the inner core to obtain a phase change composite material; The method for preparing the graphitized carbonaceous yarn comprises cutting a CNT film or a graphene film; The steps of twisting the CNT film or graphene film into thin threads and connecting the ends, twisting again to obtain yarn and graphitizing it; or The preparation method of the graphitized carbon yarn comprises the steps of cutting a CNT film or a graphene film; twisting the CNT film or the graphene film into thin threads and connecting the threads end to end, twisting the threads again to obtain yarns, loading graphene oxide and graphitizing the yarns.
2. The phase change composite material according to claim 1, characterized in that: The organic phase change material is a mixture of alkanes having 18 to 30 carbon atoms; or The organic phase change material is polyethylene glycol; the alkane mixture with 18 to 30 carbon atoms is paraffin or a paraffin derivative.
3. The phase change composite material according to claim 1, characterized in that: The inner diameter of the hollow polymer fiber is 0.2-0.4 mm; The outer diameter of the hollow polymer fiber is 0.3-0.6 mm.
4. The phase change composite material according to claim 1, characterized in that: The carbonaceous yarn is composed of yarn obtained by twisting a carbon nanotube film or a graphene film; the twist of the carbonaceous yarn is 3000-4000; the surface of the yarn is coated with graphene; the width of the carbon nanotube film or the graphene film is 5-20mm.
5. The method for preparing the phase change composite material according to claim 1, characterized in that: The method comprises the following steps: graphitizing the carbon yarn, and then winding the graphitized carbon yarn around an inner core to obtain a phase change composite material.
6. The method for preparing the phase change composite material according to claim 5, characterized in that: The preparation method of the graphitized carbon yarn comprises the steps of cutting a CNT film or a graphene film; twisting the CNT film or the graphene film into thin threads and connecting the ends thereof, twisting the threads again to obtain a yarn and graphitizing the yarn; or The preparation method of the graphitized carbon yarn comprises the steps of cutting a CNT film or a graphene film; twisting the CNT film or the graphene film into thin threads and connecting the threads end to end, twisting the threads again to obtain yarns, loading graphene oxide and graphitizing the yarns.
7. The method for preparing a phase change composite material according to claim 5, characterized in that: The method for preparing the inner core comprises the step of impregnating the hollow polymer fiber with a phase change material; or the method for preparing the inner core comprises the step of coaxial wet spinning.
8. The method for preparing a phase change composite material according to claim 5, characterized in that: The method further comprises the step of surface treating the yarn coated with graphene oxide; The surface treatment step includes multiple immersion and drying steps.
9. The method for preparing a phase change composite material according to claim 6, characterized in that: During the winding, the speed of the synchronous motor, the moving speed of the slider and the yarn diameter satisfy the following formula: T=1000L / d; Where T is the speed of the synchronous motor, L is the moving speed of the slider, and d is the yarn diameter; The winding temperature is 180-200°C.
10. The use of the phase change composite material according to claim 1, characterized in that: For thermal management; or For temperature regulation; or Heat dissipation for electronic equipment; or Equipment for energy storage and conversion; or Used in temperature control and maintenance of medical equipment.
Citation Information
Patent Citations
Composite phase change material based on kapok fiber encapsulation and SiO2 end capping and preparation method thereof
CN112724934A
Knittable multi-wall carbon nanometer modified composite phase change material and preparation method thereof
CN108360082A
Flexible linear material of liquid fluid, liquid fluid composite yarn forming method and application
CN113026164A